Improving the quality of user experience by deploying an open access network framework in a Fiber-To-The Home environment in Malaysia - Ismail, Zahid; Chik, Razmi (2011)
Content delivery via High-Speed Broadband Fiber-to-the-Home Services in Malaysia has yet to improve the Quality of Experience of the average subscribers as static contents, program menus, and channel packages delivered cannot address relevant and personalized contents to diversified subscribers in their needs and goals. Furthermore there is no common open service platform to integrate contents from licensed service providers and independent content providers alike. The objective of this research is to examine an open access network strategy that can improve the Quality of Service delivered and increase the level of Quality of Experience of the subscribers. The Open Access Network strategy will allow subscriber the freedom to select any service provider on the network. The deployment of an open-access based Active Optic Networks (AON) Fiber-To-The-Home model to individual homes enable subscribers to personalize and customize contents based on personal preference in real-time. Content management strategy such as video-based content convergence, streaming and on demand video content management and customization will significantly improve customer level of experience. In the future this study will be used as input by high speed broadband service providers in analyzing methods to increase their service delivery revenue by increasing the level of subscriber satisfaction.